Development of Print Modules into Electronic Modules in Food Microbiology Courses - Rosel, Ruhul Fitri Rosel; Faridah, Anni; Kasmita; Ambiyar (AI Society & STMIK Indonesia, 2023)
Food microbiology is one of the compulsory and important subjects as a basis for advanced courses such asFood Control, Food Preservation and Food Technology. Students experience difficulties in understanding learning material because there is no valid and practical media to use. To overcome this problem, media development was carried out in the form of E-modules for Food Microbiology Courses. The aim of this research is to develop E-module on Food Microbiology course in terms of material, format and presentation. This research uses the methodResearch and Development. E-module development using 4D models. Number of test validatorsvalidity 6 lecturers, consisting of 3 media test validator lecturers and 3 material test validator lecturersas well as 27 students majoring in Culinary Management. The average result of the assessment of material validation is 0.84 with the Valid category. Data were analyzed using the Aiken's V formula. The average result of the E-module validation assessment was 0.85 in the Valid category. The overall average result of the E-module validation on Food Microbiology Course is 0.84 with the Valid category. The average percentage of practicality by lecturers is 86.3% in the very practical category while the average practicality by students is 83.29% in the very practical category. Based on the results of all analyzes canconcluded E-module Food Microbiology Course is suitable for use in learning.